Targeting dopamine transporter to ameliorate cognitive deficits in Alzheimer's disease - Shaikh, Ammara; Ahmad, Fairus; Teoh, Seong Lin; Kumar, Jaya; Yahaya, Mohamad Fairuz (Frontiers in Cellular Neuroscience, 2023)
Alzheimer's disease (AD) is characterized by the pathologic deposition of amyloid and neurofibrillary tangles in the brain, leading to neuronal damage and defective synapses. These changes manifest as abnormalities in cognition and behavior. The functional deficits are also attributed to abnormalities in multiple neurotransmitter systems contributing to neuronal dysfunction. One such important system is the dopaminergic system. It plays a crucial role in modulating movement, cognition, and behavior while connecting various brain areas and influencing other neurotransmitter systems, making it relevant in neurodegenerative disorders like AD and Parkinson's disease (PD). Considering its significance, the dopaminergic system has emerged as a promising target for alleviating movement and cognitive deficits in PD and AD, respectively. Extensive research has been conducted on dopaminergic neurons, receptors, and dopamine levels as critical factors in cognition and memory in AD However, AD has not fully understood movement abnormalities and other features of extrapyramidal symptoms. Recently, a previously overlooked element of the dopaminergic system, the dopamine transporter, has shown significant promise as a more effective target for enhancing cognition while addressing dopaminergic system dysfunction in AD.